The Application of Let's Read! in Extensive Reading Class: Integrating MALL and Task-based Learning - Ermerawati, Anesti Budi (Universitas Pendidikan Indonesia, 2019)
Doing national program so called School Literacy Movement (GLS), classes are expected to do 15-minute regular reading activity every day; including English classes in elementary schools. Witnessing that some classes are having limited English story books to read as well as ready-to-use follow-up activities, this article proposes reading activities using e-book application Let’s Read! that can be applied after the regular reading activities. Ranging from the low leveled-books to the advanced ones, the proposed activities in this extensive reading class are integrated; combining tasks that require children to experience Mobile Assisted Language Learning (MALL) as well as having both individual and group offline work. This type of reading activity promotes L2 learner language development, increases their motivation in reading, and helps them build reading habits. At the same time, the alpha generation maximizes the use of technology to get themselves updated with the changing use of online applications such as Let’s Read!